t + 4 |
- t |
t + 2 |
1 + | t - 4 |
t2 - 4 |
t + 4 |
- t = | t + 4 |
- | t(t + 2) |
= | t + 4 - (t2 + 2t) |
= | t + 4 - t2 -2t |
= | - t2 - t + 4 |
t + 2 | t + 2 | t + 2 | t + 2 | t + 2 | t + 2 |
1 + | t - 4 |
= | t2 - 4 |
+ | t - 4 |
= | t2 - 4 + t - 4 |
= | t2 + t - 8 |
t2 - 4 | t2 - 4 | t2 - 4 | t2 - 4 | t2 - 4 |
- t2 - t + 4 |
t + 2 |
t2 + t - 8 |
t2 - 4 |
- t2 - t + 4 |
÷ | t2 + t - 8 |
t + 2 | t2 - 4 |
- t2 - t + 4 |
× | t2 - 4 |
= | - t2 - t + 4 |
× | (t - 2)(t + 2) |
= | (t - 2) (- t2 - t + 4) |
t + 2 | t2 + t - 8 | t + 2 | t2 + t - 8 | t2 + t - 8 |